2012
DOI: 10.3366/cor.2012.0017
|View full text |Cite
|
Sign up to set email alerts
|

Translator-oriented, corpus-driven technical glossaries: the case of cooking terms

Abstract: Although there are many English–Portuguese technical glossaries on the market, very few are designed to meet the specific needs of translators, whose main task is the production of an idiomatic text either in the mother tongue or in the foreign language. For that purpose, a mere list of monolexical terms (usually based on previous compilations or abstract conceptual schemata, and their equivalents) will not suffice. Most importantly, the producer of a text needs to know how a word is used in context, and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Furthermore, since our main goal was to collect texts representing the language used in the area being studied as proposed by Tagnin and Teixeira (2012), we chose texts being used every day by the community of migrants, refugees, and people working with this audience. This way, our corpus would have a greater chance of being a representative sample of the most recurrent features of the language used by these populations.…”
Section: Corpus Linguistics To Build Multilingual Corporamentioning
confidence: 99%
“…Furthermore, since our main goal was to collect texts representing the language used in the area being studied as proposed by Tagnin and Teixeira (2012), we chose texts being used every day by the community of migrants, refugees, and people working with this audience. This way, our corpus would have a greater chance of being a representative sample of the most recurrent features of the language used by these populations.…”
Section: Corpus Linguistics To Build Multilingual Corporamentioning
confidence: 99%
“…Para tanto, adotou-se uma metodologia orientada pelos pressupostos gerais da Linguística de Corpus (BERBER SARDINHA, 2004) e sua relação com a Fraseologia (TAGNIN, 2005(TAGNIN, , 2011(TAGNIN, , 2012 direcionam para um público geral de leitores, em grande parte formado também por não especialistas. Além disso, a política, sendo de natureza interdisciplinar, produz um discurso que se constitui no cruzamento de outros domínios, como o direito, as ciências sociais, a linguística, dentre outros (DORNA, 1995;CHARAUDEAU, 2006).…”
Section: Metodologiaunclassified
“…We found that the sub-corpora representing the terms "High Frequency Trading" and "bluechips" lie far away from the bulk of the data and might be regarded as outliers. This might be the result of very technical terms used in such sub-corpora since it is well-known that the more specialized the text, the greater the difference it exhibits in terms of terminological sources (Tagnin & Teixeira, 2012). For such texts the meaning might be inferred from the observation of several authentic examples in the corpus since in such cases the mere use of correct terminology does not guarantee in itself a good translation (Byrne, 2006).…”
Section: Journal Of Language Teaching and Researchmentioning
confidence: 99%
“…This helps in identifying collocations or word associations. This is an important step since the translator is essentially a text producer and needs to know how words are used and how words associate with other words (Tagnin & Teixeira, 2012). Das (2012, p. 325) defines a collocation as "a set of words occurring together more often than by chance in a corpus."…”
Section: Journal Of Language Teaching and Researchmentioning
confidence: 99%